A DEMERSAL TRAWLING GEAR FOR INSHORE WATERS ALONG THE WEST COAST - MHALATHKAR, H N; MATHAI, T JOSEPH; GEORGE, T P; ABBAS, M SYED (Fishery Technology, 2017)
Results of comprehensive efficiency tests of three tested designs of 15 m bulgedbelly, 15.8m six seam and 29.26 m longwing type trawls in combination with 114x 57 cm both rectangular flat and horizontal curved wooden otter boards are reported. Of the possible six combinations, the bulged-beHy trawl with flat rectangular otter boards has performed better in landing prawns. Further this study has indicated the selective action of the different designs.